Solve this system by substitution. y = 3 y = -3x + 6 *Remember to write your answer as a coordinate point (x, y). I​

Respuesta :

Space

Answer:

(1, 3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Coordinates (x, y)
  • Solving systems of equations using substitution/elimination

Step-by-step explanation:

Step 1: Define Systems

y = 3

y = -3x + 6

Step 2: Solve for x

  1. Substitute in y:                                                                                                 3 = -3x + 6
  2. [Subtraction Property of Equality] Subtract 6 on both sides:                      -3 = -3x
  3. [Division Property of Equality] Divide -3 on both sides:                                1 = x
  4. Rewrite/Rearrange:                                                                                        x = 1

Step 3: Solve for y

  1. Define original equation:                                                                               y = -3(1) + 6
  2. Multiply:                                                                                                           y = -3 + 6
  3. Add:                                                                                                                 y = 3